Penerimaan Ibu Rumah Tangga Terhadap Iklan Flash Sale Shopee Di Televisi Di Era Pandemi Covid-19 - Remon Remon (STAI Bumi Silampari, 2021)
Changes in people's lifestyles in social interaction through the internet, especially in the economic field. The existence of physical distancing, social restrictions and the application of health protocols make people prefer to use the internet as a support for meeting the needs of daily life. The lifestyle that is felt by the community today is a consumptive lifestyle because of the large number of mass media that intervene in shaping the construction of a lifestyle in society. With the principle of Indonesian society that still adheres to a patriarchal ideology, of course placing women as someone who is easily influenced by the game of capitalism. Through this research, see how housewives accept the Shopee flash sale advertisement on television in the current pandemic era. This research uses reception analysis research method. The results of this study are women (housewives) are still used as objects and even targets of the capitalist industry with the acceptance of women towards consumer culture through online shopping consumptive behavior. Meanwhile, the media is still a tool used to become women as ideological objects.